Recurrent Antiviral-Resistant Genital Herpes in an Immunocompetent Patient - Kriesel, John D. (J Infect Dis, 2005)
Herpes simplex virus type 2 (HSV-2) resistance to antiviral drugs has been described primarily in immunocompromised patients. We report an apparently immunocompetent, human immunodeficiency virus–negative male patient who has experienced repeated HSV-2 genital outbreaks despite receiving antiviral prophylaxis with several different drugs. Several of the HSV-2 genital isolates from this patient have been confirmed as resistant to acyclovir and penciclovir. Antiviral resistance occurred in the setting of long-term prednisone treatment and intermittent acyclovir prophylaxis at suboptimal doses and persisted despite the cessation of oral steroid treatment. The patient’s genital herpes outbreaks were not controlled by high-dose prophylaxis with acyclovir, valacyclovir, and famciclovir. Cessation of antiviral prophylaxis resulted in reversion of this patient’s HSV-2 isolates to acyclovir and penciclovir sensitivity, although resistant virus reappeared when antiviral prophylaxis was resumed. Transmission of a sensitive HSV-2 strain from this patient to a female sex partner was observed. These observations confirm previous reports that resistance to acyclovir may develop during prophylactic therapy in an otherwise well, immunocompetent patient. These findings support the conclusion that both drug-sensitive and drug-resistant HSV-2 strains established latency in this patient and that both strains are capable of frequent reactivation.